Co-designing implementation strategies to promote remote physical activity programs in frail older community-dwellers - Villa-García, Lorena; Davey, Vanessa; Peréz, Laura M.; Soto-Bagaria, Luis; Risco, Ester; Díaz, Pako; Kuluski, Kerry; Giné-Garriga, Maria; Castellano-Tejedor, Carmina; Inzitari, Marco (Frontiers in Public Health, 2023)
Background: The “AGIL Barcelona (AGILBcn)” community-based integrated care program is a multicomponent healthy aging intervention for frail older adults. This study aimed to identify implementation strategies to optimize the accessibility, acceptability, and adaptability of mhealth interventions to enhance physical activity in frail older adults, and to prioritize action points according to importance and feasibility through a co-design process. Material and Methods: A mixed methods approach was applied. In the qualitative phase, a method adapted from the World Café was applied in 6 virtual groups to identify strategies to facilitate the virtual physical activity program. In the quantitative phase, prioritization and feasibility of the strategies was analyzed through surveys. Strategies were ranked based on value vs. complexity, revealing if strategies should be implemented first, if possible or taken into account for future consideration, or directly disregarded. The convenience sample included older adults (n=7), community professionals (n =9) and health professionals (n=13). Qualitative data were analyzed by summative content analysis and quantitative data by nonparametric descriptive analyses. Results: A total of 27 strategies were identified and grouped into: general strategies for reducing barriers; specific strategies for facilitating the use of a digital application; specific strategies for facilitating the participation in virtual exercise groups and specific strategies for facilitating external support. These were prioritized as needing attention first: digital literacy, digital capability assessment, family technology support, weekly telephone follow-up by professionals, personalizing exercises, virtual exercises in small groups. Conclusion: The active participation of all stakeholders enabled us to identify strategies to maximize the probability of successful implementation of person-oriented technology in the AGILBcn physical activity program though an increased engagement of participating older adults